(untitled) (Medical Forum Monthly, 2024)
Objective: To find out frequent pelvic pathologies in primary infertility on diagnostic laparoscopy. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Health Care Centre Mardan from November 2015 to October 2016. Materials and Methods: Total of 65 patients with primary infertility was selected. Patients with previous abdominal surgeries and medical comorbidities were excluded. After thorough gynecological examination, necessary investigations were done. Laparoscopy was done on day 10 of menstrual cycle calculated from last menstrual period (LMP) through sub umbilical incision. Data was collected in terms of age, duration of infertility. Results: Majority of patients were in age group of 26-33 [64%]. Mean age was 28 years (range18-40). About 41 percent of patients had active marital life of 5-7 years duration. 53 percent had normal findings on laparoscopy. Among the various pathologies most commonly observed was block tube contributing to about 23%. Out of which 9.2% had blocked tubes without adhesions and 13% had blocked tubes with adhesions .next frequent pathology was PCOS contributing to about 7 (10.8%). Uterine pathologies like fibroid, anomalies were seen in 6.7% and endometriosis in 2.7%. Conclusion: The most frequent pathology seen in primary infertile patients in diagnostic laparoscopy is tubal blockage.